Biochemical Composition of Seaweeds along the Southwest Coast of India - Rao , Swapna; Anantharaman, P. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Seaweeds have been utilized traditionally for food, fertilizer, and various industrial applications. In recent years, there has been growing interest in their potential as a source of bioactive compounds with applications in the food, pharmaceutical, and cosmetic industries. Additionally, seaweeds are being explored for their environmental benefits, such as their role in carbon sequestration and wastewater remediation. In the present study, three biochemical components: Protein, Carbohydrate, and Lipids were tested in five seaweed species (Grateloupia lithophila, Gelidium pusillum, Ulva flexuosa, Gracilaria corticata, and Ceratodictyon variabile) belonging to Phylum- Rhodophyta and Chlorophyta. It was found that the Carbohydrate content was higher in species belonging to Phylum- Rhodophyta, ranging from 63.6 mg/g to 376.4 mg/g, and lower in Species belonging to Phylum-Chlorophyta with a value of 56.68 mg/g. The protein content showed a similar pattern of data, with Protein content higher in species belonging to Phylum-Rhodophyta and lower in Species belonging to Phylum-Chlorophyta. The protein content ranged from 28.05 mg/g to 58.32 mg/g. whereas, the opposite was seen in the case of lipids. Lipid content was recorded to be higher in Chlorophyta and lower in Rhodophyta, with values ranging from, 5.1 mg/g to 62.6 mg/g.